2014
DOI: 10.1186/1754-6834-7-51
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of biodegradation performance of furfural and 5-hydroxymethylfurfural by Amorphotheca resinae ZN1

Abstract: BackgroundFurfural and 5-hydroxymethylfurfural (HMF) are the degradation products of lignocellulose during pretreatment operations and significantly inhibit the consequent enzymatic hydrolysis and fermentation processes. The biodetoxification fungus Amorphotheca resinae ZN1 had demonstrated its excellent capacity on degrading lignocellulose derived inhibitors and helped the fermentation processes to achieve high yield of ethanol and biochemicals. Analysis of the biological degradation performance of furfural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 44 publications
5
73
1
5
Order By: Relevance
“…Aerobic and anaerobic microorganisms ( Coniochaeta ligniaria, Ureibacillus thermosphaericus, Issatchenkia occidentalis, Enterobacter sp.) have been used for the removal of furfural and 5‐HMF from hydrolysates obtained from lignocellulosic biomass . These microorganisms use the metabolic pathway of Trudgill, which consists of various stages of oxidation and reduction catalyzed by enzymes such as aldehyde dehydrogenase, furoyl‐CoA synthetase or furoyl‐CoA dehydrogenase for the degradation of these compounds.…”
Section: Technologies For Inhibitor Removal From Hydrolysatesmentioning
confidence: 99%
“…Aerobic and anaerobic microorganisms ( Coniochaeta ligniaria, Ureibacillus thermosphaericus, Issatchenkia occidentalis, Enterobacter sp.) have been used for the removal of furfural and 5‐HMF from hydrolysates obtained from lignocellulosic biomass . These microorganisms use the metabolic pathway of Trudgill, which consists of various stages of oxidation and reduction catalyzed by enzymes such as aldehyde dehydrogenase, furoyl‐CoA synthetase or furoyl‐CoA dehydrogenase for the degradation of these compounds.…”
Section: Technologies For Inhibitor Removal From Hydrolysatesmentioning
confidence: 99%
“…Recent research showed that overexpression of alcohol dehydrogenases (encoded by ADH ), transcription activator Msn2, oxidative stress regulator Yap1, and glucose-6-phosphate dehydrogenase, which were confirmed by transcriptional analysis, proteomic analysis, and disruption library screening, could improve furfural tolerance in yeast [1922]. In S. cerevisiae , furfural could be converted into furfuryl alcohol by NADH-dependent alcohol dehydrogenase 1 [2325]. Co-expression of transaldolase 1 and alcohol dehydrogenase 1 in recombinant xylose-fermenting S. cerevisiae improves the production of ethanol and xylitol in xylose medium in the presence of furfural [26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during most studies on biodegradation of furanic compounds, it was found that the reduction reaction of FAL and hydroxymethyfurfural (HMF) was often reversible. FOL can be oxidized to FAL again by alcohol dehydrogenase or aldehyde oxidase and then to FA by aldehyde oxidase from the cells . In this study, more FA produced at higher cell loading suggested that the decrease of FOL selectivity might be owing to the proceeding oxidization of produced FOL to FA.…”
Section: Resultsmentioning
confidence: 58%
“…In the case of glucose and maltose, the higher conversion was due to the much greater ability of S. cerevisiae to consume glucose and maltose than ethanol. However, ethanol is often an inhibitor for cell growth . To our knowledge, glucose is a broad‐spectrum carbon source and is less expensive than maltose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation